Community engagement in health promotion campaigns: A qualitative photo content analysis from vitalizing communities against NCD risk factors (V-CaN) field trial in rural central India - Aditya V. Samanthapudi; Devyani Wanjari; Radhika Sharma; M Rajashekhar; Ashwini Kalantri; Abhishek V. Raut; Subodh S. Gupta (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: India faces a critical challenge with 5.8 million annual deaths from non-communicable diseases (NCDs). Maharashtra, where NCDs constitute 66% of the disease burden. The youth, lacking awareness, are vulnerable. Vitalizing communities against NCD risk factors (V-CaN) melawa, inspired by the "Pandharpur Wari" pilgrimage, aims to bridge implementation gaps and empower communities. "Arogya chi wari" integrates health practices with cultural events, offering a unique approach. Photo documentation from V-CaN melawa becomes a powerful tool for assessing community engagement qualitatively. The aim of the study was to qualitatively analyze photos from V-CaN melawas, exploring community engagement in health promotion against NCD risk factors. MATERIALS AND METHODS: V-CaN melawas were organized in the field practice area of the department of community medicine. These melawas were part of the cluster randomized field trial named V-CaN, which is being implemented in a rural area of the Wardha district of Maharashtra. The V-CaN days, also known as melawas, were organized with the aim of facilitating behavioral change among participants. A qualitative study using photo content analysis was conducted, reviewing 2000 pictures from 59 V-CaN melawas. Thematic content analysis was employed, with researchers selecting 61 photos based on uniqueness. RESULTS: Six major themes emerged: health promotion, health system involvement, intersectoral coordination, inclusiveness, community resource mobilization, and innovation. Examples include nutrition exhibitions, health screenings, and innovative games. CONCLUSIONS: The analysis showcases diverse community participation in V-CaN melawas, emphasizing inclusivity, collaboration, and innovation. While qualitative, the study lays the foundation for future quantitative assessments of the intervention's impact on health outcomes and community attitudes.